Poison princess - Cole, Kresley (Cole, Kresley. Arcana chronicles., 2012)
In the aftermath of a cataclysmic event, sixteen-year-old Evie, from a well-to-do Louisiana family, learns that her terrible visions are actually prophecies and that there are others like herself--embodiments of Tarot cards destined to engage in an epic battle.